Teacher Competency in Implementing Islamic Education Learning - Based on Higher Order Thinking Skills (HOTS) at Junior High School - Sulaiman, Akh. (International Journal of Science, Engineering, and Information Technology, 2025)
Teachers play an important role in ensuring the effectiveness and quality of the learning process and outcomes. Quality learning can be realized if teachers have strong competence in their fields of study, especially pedagogical competence that is closely related to learning practices. This is especially relevant in the context of Islamic Religious Education (PAI), where Higher Order Thinking Skills (HOTS)-based learning needs to be studied further at the junior high school level. This study aims to examine the pedagogical competence of teachers in the planning, implementation, and evaluation stages of HOTS-based PAI learning, as well as to identify the factors that influence these competencies at SMP Negeri 2 Pegantenan, Pamekasan. Using a qualitative research design with a phenomenological approach, the results of the study showed that the pedagogical competence of teachers in planning HOTS-based PAI learning was classified as good, as evidenced by the preparation of a good lesson plan (RPP). The implementation of PAI learning is in accordance with the planned strategy, which shows that the implementation of learning in the classroom is going well. Likewise with the evaluation of learning that has been carried out well.  This study also identified several factors that influence teachers' pedagogical competence in HOTS-based Islamic Religious Education learning, including student characteristics, environmental context, teacher qualifications, and school policies.